Sistem Informasi Iklim dan Kualitas Udara pada Laboratorium Kalibrasi BMKG Berbasis Website - M. Audi Ikhsan; Samsudin, Samsudin (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
To ensure the reliability of measurement results, the calibration laboratory of the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) requires accurate control of temperature and humidity. Conventional manual monitoring methods are susceptible to errors caused by human interaction and environmental fluctuations. To address this challenge, a web-based monitoring system has been developed. This system automates the measurement of temperature and humidity, thereby increasing efficiency and reducing the risk of human error. Two prototype meters have been integrated into the system, which have been proven to have an accuracy of over 90% for temperature measurements. The system is capable of measuring humidity in the range of 0% to 100% with an accuracy of ±5% and temperature in the range of -40°C to 80°C with an accuracy of ±0.1°C. By automating the monitoring process and providing real-time data access, this system makes a significant contribution to improving the reliability and efficiency of the BMKG calibration laboratory. The implementation of this system is expected to ensure the consistency of calibration measurement results, support the optimal functioning of the laboratory, and contribute to improving the quality of meteorological, climatological, and geophysical services in Indonesia.